The Analysis of Educational Facilities and Infrastructure Standards at SMP Negeri 9 Pekanbaru - Moza Rifanni Rezpa; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The fulfillment of educational facilities and infrastructure standards constitutes a fundamental prerequisite for quality and equitable learning processes. This study aims to analyze the condition of facilities and infrastructure at SMP Negeri 9 Pekanbaru within the framework of the 6th National Education Standard (SNP) as regulated by Permendikbudristek Number 22 of 2023. The research employed a mixed methods approach with a sequential explanatory design, combining quantitative data analysis from Dapodik Kemendikdasmen and the Infrastructure Management Information System (SIMSARPRAS) of the Pekanbaru City Education Office, with qualitative document analysis of relevant regulations and academic literature. SMP Negeri 9 Pekanbaru was established in 1981, is located in Tenayan Raya District, and received Grade A accreditation in 2021 with a final score of 92. Dapodik data for Semester 2025/2026 (Even) indicates the school serves 1,086 students, 47 teachers, and 13 administrative staff, with a total of 75 infrastructure units including 28 classrooms and 4 laboratories. Findings indicate that the school generally possesses adequate core infrastructure, yet several components require improvement, including the health room, library, administrative office, and various furnishings in moderate to severe disrepair. This study formulates concrete recommendations for relevant stakeholders to promote sustainable SNP compliance.